Pengembangan Media Pembelajaran Matematika Siswa SMP Berbasis Android - Siti Komariah; Huri Suhendri; Arif Rahman Hakim (Universitas Indraprasta PGRI, 2018)
This research aims to develop an Android-based learning media with software Construct 2 material number for the students of Junior High School classes VII, VIII, and IX. This research use approach to research and development (research and development) with the ADDIE model of development: (1) analysis (analysis), including: needs analysis, analysis of the characteristics of the students, and curriculum analysis, (2) design ( the design), include: the creation of flowcharts, storyboards, interface design, and (3) development (development), include: the collection of material, product creation and revision, (4) implementation (implementation), in this case the researchers don't do stage implementation because of lack of time, (5) evaluation (evaluation), include the following: assessment by the expert question form material, media quality assessment now learning by the media, and now experts design development. Based on the assessment carried out by the experts, it can be concluded that the design of learning mathematics.